Sustained cereal bowl amidst global warming - Pasion-Uy, Erstelle A.; Uy, Lawrence Yves C.; Kavi Kishor, Polavarapu B.; Fernie, Alisdair R.; Sreenivasalu, Nese (Cell Press, 2025)
High day and night temperatures impair grain yield and quality in major cereal crops such as rice, maize, and wheat, posing a major challenge under global warming. In this review, we have highlighted advances that govern flowering through clock genes, key genetic regulatory mechanisms of the complex processes that regulate inflorescence architecture and grain filling efficiency, which are affected by heat stress. This unraveled knowledge offers opportunities to improve grain yield and quality without tradeoffs, leading to higher grain number, more efficient grain filling, and maintaining uncompromised starch-to-protein accumulation under high day and night temperatures.